Wacana Posmodernisme dalam Pemikiran Pendidikan Islam - Arhanuddin Salim (Journal of Islamic Education Policy, 2017)
ABSTRACT, This study is part of an academic endeavor to discover a new postulate as part of the development and reformation of Islamic educational thinking. Postmodernism as a mode of contemporary discourse in the social sciences and humanities can serve as the base of thougth in strengthening the epistemology of Islamic education scholarship. The main purpose of this study is to further examine Islamic Education as a scientific building that must be separated from the theological aspects that surround it.Keywords: Posmodernism, discourse, Islamic education